A comprehensive review of usefulness of sodium butyrate for the management of inflammatory bowel disease: from molecular mechanisms to clinical application - Karłowicz, Katarzyna; Lewandowski, Konrad; Tulewicz-Marti, Edyta; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2026)
Sodium butyrate (SB), a salt of the short-chain fatty acid butyrate, has emerged as a promising adjunctive therapy in inflammatory bowel disease (IBD). IBD is commonly associated with intestinal dysbiosis characterized by depletion of butyrogenic bacteria. This leads to a functionally relevant butyrate deficiency that contributes to epithelial barrier dysfunction, immune dysregulation, and persistent mucosal inflammation. Experimental studies demonstrate that butyrate supports colonocyte energy metabolism, strengthens tight-junction integrity, enhances mucin and antimicrobial peptide production, and promotes epithelial repair. These effects are mediated through immunomodulatory pathways, in particular involving G-protein–coupled receptor activation and histone deacetylase inhibition. Clinically, SB has shown therapeutic potential primarily in ulcerative colitis, with more limited data in Crohn’s disease. This review summarizes current evidence regarding the clinical utility of SB supplementation in patients with IBD and outlines the mechanistic basis supporting its therapeutic application.